Covid-19 UMP activates virtual classes - TN, Alagesh (News Straits Times Press (Malaysia) Sdn. Bhd., 2020)
KUANTAN: Universiti Malaysia Pahang (UMP) is the latest higher learning institution in the country to activate e-learning for its students in a move to curb the spread of Covid-19.